Performance analysis of various domestic lighting luminaires / Kevin Kumar Santiago George - Kevin Kumar, Santiago George (2018)
Lighting consumes nearly 20% of total power consumption around the world and with the advancement of technology in this present day, there is a high probability that abundant energy savings can be achieved. Over the years, these lighting fittings have progressively been improved in terms of their efficiency, cost, brightness and other contributing factors. However, there are certain population of the public who still rely on old technology as there are not many made aware of the benefits. These are more prominent in the 3rd world countries that do not have the latest technology in hand. Based on their limited knowledge, the older technology in reality is consuming more power and the cost of maintaining the fitting is higher. The focus of this report is on the advancement of lighting luminaires present in the market. This report entails a thorough comparative analysis focusing on the major usage of lamps such as Incandescent Lamp (IL), Fluorescent Lamp (FL) and Light Emitting Diodes (LED). Other types of lamps are also compared in this report for analysis purposes. This report presents the utilization of lighting design software DIALux to carry out the tests of various lamps made available in the market in the present day. Results portray that utilizing LED lamps are key to obtain lower power consumption, reduce cost, and reduce number of fittings all whilst keeping an area of space well lit. The advancement in the development of LED lamps is progressing at a rapid pace and can be foreseen to lead the lighting industry in the years to come.